2010
DOI: 10.5399/osu/jtrf.46.1.971
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Contributions to Container Port Capacity: A Survey of Port Authorities

Abstract: Given recent concerns about

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…An essential aspect related to the complexity of seaports is the fact that they have a wide range of stakeholders. Stakeholders, such as port authorities, terminal operators, customs, and government ministries, use heterogeneous business information systems, and the integration of these systems presents a challenge [19]. Seaport stakeholders themselves have varying objectives, and accordingly they prioritise different port activities [20].…”
Section: Seaportsmentioning
confidence: 99%
“…An essential aspect related to the complexity of seaports is the fact that they have a wide range of stakeholders. Stakeholders, such as port authorities, terminal operators, customs, and government ministries, use heterogeneous business information systems, and the integration of these systems presents a challenge [19]. Seaport stakeholders themselves have varying objectives, and accordingly they prioritise different port activities [20].…”
Section: Seaportsmentioning
confidence: 99%
“…Ports enable low-cost, rapid transport of goods critical to global supply chains. Yet previous research has demonstrated insufficient network-wide port capacity planning (Maloni and Jackson 2005b), which will increase lead times and subsequent pipeline and safety stock inventory costs. As an extreme example, a two-week labor lockout in 2002 at US West Coast ports disrupted 300,000 shipments (Gooley and Cooke 2002) at an estimated economic cost of $1 billion per day (Keane 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In 2009 US ports handled more than 37 million twenty foot equivalent unit (TEU) containers (American Association of Port Authorities 2009), carrying more than $500 billion in goods. System-wide port infrastructure capacity challenges, however, have caused cargo congestion problems in the past decade (Bernstein 2006;Maloni and Jackson 2005a). Although weak economic conditions in recent years have temporarily alleviated congestion concerns, the looming rebound in trade growth without proactive investment in national port and transportation infrastructure will likely again lead to strained port capacity (US Chamber of Commerce 2008; US Department of Transportation Maritime Administration 2007; "US Ports Expand Capacity to Meet Growing Demand" 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations